CC. PP. Achual Tipishca - Río Huallaga - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se puede ver el Río Huallaga y el centro poblado Achual Tipishca
ENGLISH: You can see the Huallaga River and the village of Achual Tipishca.

SPANISH: Se puede ver el Río Huallaga y el centro poblado Achual Tipishca
ENGLISH: You can see the Huallaga River and the village of Achual Tipishca.
CC. PP. Achual Tipishca - Huallaga River
Keywords: Iquitos (Perú)|~|Architecture|~|Rural|~|Amazon|~|Nature|~|Jungles|~|Paisajes|~|Iquitos (Perú)|~|Iquitos (Perú)|~|arquitectura|~|rural|~|naturaleza|~|junglas